Nurses' Perceptions of Interventions for the Management of Patient‐Oriented Outcomes: A Key Factor for Evidence‐Based Practice. Issue 1 (14th January 2016) - Sidani, Souraya; Manojlovich, Milisa; Doran, Diane; Fox, Mary; Covell, Christine L.; Kelly, Helen; Jeffs, Lianne; McAllister, Mary
ABSTRACT: Background: Various barriers and facilitators to implementing evidence‐based interventions in practice have been acknowledged. Nurses' perspectives on these interventions were overlooked as potential factors that influence their uptake in practice. The purpose of this study was to explore nurses' perception of evidence‐based interventions targeting patient‐oriented outcomes. Methods: A mixed method design involving concurrent application of quantitative and qualitative approaches was used. Nurses ( n = 56) working in acute and rehabilitation care settings completed the Intervention Acceptability scale and responded to open‐ended questions. The scale presented information on the components, activities, dose, and mode of delivering evidence‐based interventions targeting each patient‐oriented outcome (fatigue, nausea and vomiting, dyspnea, pain, physical function, self‐care) and items to rate the interventions on five attributes (relevance, applicability, frequency of use, likelihood, and comfort in implementation). The open‐ended questions inquired about the appropriateness and resources needed to use the interventions in practice. Results: The quantitative results indicated favorable perceptions of most interventions. Nurses rated acupressure, guided imagery, massage, and relaxation as having limited appropriateness and they reported low levels of comfort in applying them. The qualitative themes clarified the reasons underlying nurses' ratings. Linking Evidence to Action: This study's findings highlight the importance of examining nurses' perceptions of evidence‐based interventions as an initial step toward promoting the adoption of interventions in practice. Effective interventions that are considered of limited relevance are unlikely to be implemented in practice. Nurses' perceptions can guide the design or selection of dissemination strategies to clarify any misconception about the effectiveness and risk of evidence‐based interventions.